Happy Studio: Positive psychology in project design - Soto Buzzetti, José (Base Diseño e Innovación, 2016)
Happy Studio is a methodology that seeks to position happiness as a valuable asset in the creation of design, innovation and social development projects, through the symbiosis between positive psychology and strategic design tools. The basal concern of this methodology is: How to be happier developing creative processes? To respond to this question, we propose the implementation of methodological resources that enhance creative processes, inserting the search of individual and collective happiness at the beginning of project process creation. Thus, we seek that these have a strong link with the intrinsic motivations, strengths and skills of the participants. This type of projects are called "happy projects". This text presents the Happy Studio experience in seminar and final project design studios, at the Design School, Universidad Diego Portales. In this course, we guide students in the formulation and development of happy professional projects, I.E. Offer them the possibility of obtaining their graphic or industrial designer degree and, in addition, integrate the pursuit of happiness, both in the process and in its outcome.
Keywords: positive psychology; education; design; design thinking